2006
DOI: 10.1111/j.1365-2109.2006.01460.x
|View full text |Cite
|
Sign up to set email alerts
|

Spermatophore cryopreservation and artificial insemination of black tiger shrimp, Penaeus monodon (Fabricius)

Abstract: To develop an appropriate cryopreservation protocol for spermatophores of black tiger shrimp, Penaeus monodon, three cryoprotectants (dimethyl sulphoxide (DMSO), methanol (MeOH) and ethylene glycol (EG)) at two concentrations (5% and 10%) were examined. Artificial implantation of spermatophores was also carried out to assess the fertilizing ability of fresh and post‐thaw spermatophores. Spermatophores were collected during consecutive regenerations (15‐day intervals) and assessed for qualitative and quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0
9

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 11 publications
(14 reference statements)
3
31
0
9
Order By: Relevance
“…In the present work, the mortality of sperm cells changed as the cryoprotectant concentrations and exposition times increased and the optimal concentration and equilibration time were 10% and 10 minutes, respectively. Barth et al (2006) while working with the giant tiger prawn, P. monodon, used DMSO at 5 and 10% as cryoprotectant. Results showed that DMSO at 5% offered better results when sperm survival reached 79.7%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present work, the mortality of sperm cells changed as the cryoprotectant concentrations and exposition times increased and the optimal concentration and equilibration time were 10% and 10 minutes, respectively. Barth et al (2006) while working with the giant tiger prawn, P. monodon, used DMSO at 5 and 10% as cryoprotectant. Results showed that DMSO at 5% offered better results when sperm survival reached 79.7%.…”
Section: Resultsmentioning
confidence: 99%
“…The development of methods of semen preservation and the implementation of effective artificial reproduction protocols require a good knowledge of the reproductive biology and seminal characteristics of the targeted species (Ninhaus-Silveira et al 2006). For marine shrimps, cryoprotectants dimethyl sulfoxide (DMSO) and ethylene glycol (EG) are widely used (Anchordoguy et al 1988;Barth et al 2006;Vuthiphandchai et al 2007). DMSO, when compared with glycerol, proline and trehalose, presents low toxicity to the spermatic cells of Sicyonia ingentis (Anchordoguy et al 1988).…”
Section: Introductionmentioning
confidence: 99%
“…The Ca-Fsaline (21.63 g NaCl, 1.12 g KCl, 0.53 g H 3 BO 3 , 0.19 g NaOH and 4.93 g MgSO 4 .7H 2 O in 1 L sterile distilled water (adjusted to pH 7.4 with 1 NHCl)) was prepared as the extender medium (Bart et al 2006;Memon et al 2012d). The extender was prepared one day before the collection of samples and stored in the refrigerator.…”
Section: Methodsmentioning
confidence: 99%
“…The samples were kept in LN for 30 days (Memon et al 2012b). On day 30, thawing was done by immersing the cryovial in a water bath at 30ºC for 2 min (Bart et al 2006;Memon et al 2012b). After thawing, the samples were examined under the electron microscope.…”
Section: Methodsmentioning
confidence: 99%
“…Temperature, which is one of the most important factors that affect the physiology of cell (Boon et al 2008;Fan et al 2008;Jong et al 2009;Oguchi et al 2006), is one of them (Martin et al 2001;Nagao and Munehara 2007). Low temperature has been widely used for in vitro spermatozoa storage and artificial fertilization of aquatic crustaceans (Bart et al 2006;Magda et al 2004;Nimrat et al 2006;Thomas et al 1988;Vuthiphandchai et al 2007). However, the information on the effects of temperature on AR and capacitation in crabs are sparse (Bhavanishankar and Subramoniam1997;Kang et al 2009) although aquaculture of crabs has become very important.…”
Section: Introductionmentioning
confidence: 99%